Johann Adam Möhler’s Dynamic Ecclesiology - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
Along with Kant’s sapere aude, the Enlightenment brought about a certain kind of rigidity as though everything could only be understood by way of logical reasoning through a set of inflexible procedures. When the Church was understood within this movement, it lost its dynamic and organic dimension. Romanticism, as the counter movement of the Enlightenment, brough new inspiration as to how one should do ecclesiology. Möhler took the chance. His ecclesiology is influenced by romanticism without being too abstract. His ecclesiology is exemplary of a creative ecclesiology that can manage various tensions due to different ways of understanding the nature of the Church.